INCONSISTENCY IN THE PROVISION OF RESTITUTION FOR VICTIMS OF SEXUAL VIOLENCE CRIMES IN LIGHT OF JUDICIAL DECISIONS IN INDONESIA - David Mangaraja Lumban Batu; Setiawan Noerdajasakti; Faizin Sulistio (CV. RADJA PUBLIKA, 2025)
Indonesia, as a state governed by the rule of law, is committed to protecting human rights through the Criminal Justice System. One of the main challenges is the handling of sexual violence crimes. To this end, Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS) affirms the right to restitution for victims as part of their recovery. However, implementation in practice shows differences in judicial considerations and attitudes in determining restitution, despite its clear regulation in the law. This study aims to analyze the factors hindering the implementation of restitution for victims of sexual violence crimes, with a focus on cases carrying penalties exceeding four years. This research is expected to provide recommendations to enhance law enforcement compliance in fulfilling the obligation to provide restitution, thereby better protecting victims’ rights.